Gastrointestinal Bleeding in Small Bowel Arteriovenous Malformation: A Case Report - Renaldi, Kaka; -, Aisyah (The Indonesian Society for Digestive Endoscopy, 2025)
Arteriovenous malformations of the gastrointestinal tract (AVM) can occasionally result in gastrointestinal bleeding. Less than 5% of nonvariceal upper gastrointestinal bleeding is caused by gastrointestinal AVMs, a relatively uncommon cause of GI bleeding. Clinical symptoms that they might present include intussusception, persistent anemia, overt or obscure GI bleeding, and abdominal pain. A 41-year-old male patient presented with a 7-year history of recurrent melena. An initial enteroscopy showed spurting bleeding in the jejunum with histological examination showing AVM with ectopic pancreas. The patient underwent laparotomy with resection, anastomosis, and the construction of a new duodenojejunostomy. The patient complained of recurrent melena during three years of postoperative follow-up. The patient underwent laparotomy resection of the ileum to ascending colon, ileostomy, and splenectomy. Histological examination of the bleeding duodenal mucosa confirmed an arteriovenous malformation. The patient then underwent endoscopic hemostasis using hemoclips and was treated with coil embolization. In abdominal CT, angiographic evaluation showed no visible picture of vascular malformations. Intestinal AVMs are rare but should be considered as the differential diagnosis in patients with recurrent gastrointestinal bleeding. Endoscopic hemostasis, surgical resection, and angiographic intervention can be considered as treatments for AVM.Keywords: Arteriovenous malformation, gastrointestinal bleeding, small bowel